Trichoscopic Analysis of Healthy Indian Males for Standardization of the Measurable Parameters: An Observational, Cross-sectional Study - Amina Asfiya; Malcolm Pinto; Manjunath Mala Shenoy; Spandana P Hegde; Atul Rajeendran; Fathima Shafi (Indian Dermatology Online Journal)
Background: Trichoscopy is a simple, noninvasive tool to help in the diagnosis of various hair and scalp disorders. There is paucity of data on the normal trichoscopic parameters of hair density and diameter in the Indian population. Aim: The aim of this study was to establish the trichoscopic patterns of hair and scalp in healthy Indian males and to provide a framework for future reference. Materials and Methods: Quantitative trichoscopic analysis using a videodermoscope was done on healthy Indian males with no hair/scalp complaints. Images were taken from four areas: frontal, occipital, and both temporal areas, under 20x and 70x magnification. The following parameters were analyzed by the software: hair density and thickness; percentage of thin, medium, and thick hairs; percentage of anagen and telogen hairs; vellus hair density and hair count; follicular unit density; percentage of follicular hair units; single, double, triple, and four hairs per follicular unit; and distribution and pattern of scalp vasculature. Results: A total of 120 healthy males were recruited in the study with a mean age of 24.6 years. The hair density was the highest in the frontal and occipital areas, while the hair thickness was similar in all the sites evaluated. The follicular unit density was the highest in the frontal and occipital areas with the temporal area having the highest number of single hair follicular units. The scalp vasculature varied with the area examined, the most common pattern being the pin-point type. Limitations: It was a hospital-based study with a relatively small sample size. The software used in the study cannot detect gray hairs. Conclusion: Our study has attempted to fill the gaps in the medical literature by proposing comparable reference values for trichoscopy in healthy Indian males.